Age‐related changes in lip morphological and physiological characteristics in Korean women - Kim, Hyerim; Lee, Myeongryeol; Park, Sun Young; Kim, Yong Min; Han, Jiyeon; Kim, Eunjoo (Skin research and technology, 2019)
Objective Age‐related changes in lip morphological and physiological characteristics are key indices for estimating age based on facial features, as reported in many studies. Yet, a majority of studies have focused on Caucasian individuals, with few studies characterizing these changes in Asian female populations. Therefore, the aim of this study was to investigate lip morphological and physiological characteristics in a cohort of Korean women. Methods A total of 114 volunteers participated in the study. Linear distances (length of philtrum, length of lip, width of lip, and lengths of lower and upper oral commissures), angle of the upper lip, 3D lip heights, and wrinkles were calculated and averaged for each age‐group. We also measured lip color, hydration, trans‐epidermal water loss (TEWL), and blood flow. Statistical analyses were performed using SPSS version 20.0 (significance level P < 0.05). Results Length of the philtrum and lip width significantly increased with age while upper and lower lip lengths and length of the lower oral commissure significantly decreased with age. The angle of the upper lip tended to decrease with age, but this finding was no significance. Three‐dimensional height of the upper lip, wrinkles, and TEWL also decreased with age while hydration increased with age. Finally, redness of the upper and lower lips as well as blood flow significantly decreased with age. Conclusion Lips tended to shorten in length and widen with age, resulting in a thinner and longer appearance. With regard to physiological parameters, there were important age‐related changes in hydration and lip color.